Resveratrol Derivatives as Potential Treatments for Alzheimer’s and Parkinson’s Disease - Arbo, Bruno Dutra; André-Miral, Corinne; Nasre-Nasser, Raif Gregorio; Schimith, Lúcia Emanueli; Santos, Michele Goulart; Costa-Silva, Dennis; Muccillo-Baisch, Ana Luiza; Hort, Mariana Appel (Frontiers in Aging Neuroscience, 2020)
Neurodegenerative diseases are characterized by the progressive loss of neurons in different regions of the nervous system. Alzheimer’s disease (AD) and Parkinson’s disease (PD) are the two most prevalent neurodegenerative diseases, and the symptoms associated with these pathologies are closely related with the regions that are most affected by the process of neurodegeneration. Despite their high prevalence, currently, there is no cure or disease-modifying drugs for the treatment of these conditions. In the last decades, due to the need of development of new treatments for neurodegenerative diseases, several authors have investigated the neuroprotective actions of naturally occurring molecules, such as resveratrol. Resveratrol is a stilbene found in several plants, including grapes, blueberries, raspberries and peanuts. Studies have shown that resveratrol presents neuroprotective actions in experimental models of AD and PD, however, its clinical application is limited due to its rapid metabolism and low bioavailability. In this context, studies have proposed that structural changes in the resveratrol molecule, including glycosylation, alkylation, halogenation, hydroxylation, methylation and prenylation could lead to the development of derivatives with enhanced bioavailability and pharmacological activity. Therefore, the aim of this review is to discuss how resveratrol derivatives could represent viable molecules in the search for new drugs for the treatment of AD and PD.